Balloon catheter for induction of labor in women with one previous cesarean and an unfavorable cervix. (7th March 2019) - Huisman, Claartje M. A.; ten Eikelder, Mieke L. G.; Mast, Kelly; Oude Rengerink, Katrien; Jozwiak, Marta; van Dunné, Frédérique; Duvekot, Johannes J.; van Eyck, Jim; Gaugler‐Senden, Ingrid; de Groot, Christianne J. M.; Franssen, Maureen T. M.; van Gemund, Nicolette; et al.
Abstract: Introduction: When women with a previous cesarean section and an unfavorable cervix have an indication for delivery, the choice is to induce labor or to perform a cesarean section. This study aims to assess the effectiveness and safety of a balloon catheter as a method of induction of labor in women with one previous cesarean section and an unfavorable cervix compared with an elective repeat cesarean section. Material and methods: We performed a prospective cohort study in 51 hospitals in the Netherlands on term women with one previous cesarean section, a live singleton fetus in cephalic position, an unfavorable cervix and an indication for delivery. We recorded obstetric, maternal and neonatal characteristics. We compared the outcome of women who were induced with a balloon catheter with the outcome of women who delivered by elective repeat cesarean section. Main outcomes were maternal and neonatal morbidity. Mode of delivery was a secondary outcome for women who were induced. Adjusted odds ratios (aOR) were calculated using logistic regression, adjusted for potential confounders. Results: Analysis was performed on 993 women who were induced and 321 women who had a repeat cesarean section (August 2011 until September 2012). Among the women who were induced, 560 (56.4%) delivered vaginally and 11 (1.1%) sustained a uterine rupture. Composite adverse maternal outcome (uterine rupture, severe postpartum hemorrhage or postpartum infection) occurred in 73 (7.4%) in the balloon and 14 (4.5%) women in the repeat cesarean section group (aOR 1.58, 95% confidence interval [CI] 0.85‐2.96). Composite adverse neonatal outcome (Apgar score <7 at 5 minutes or umbilical pH <7.10) occurred in 57 (5.7%) and 10 (3.2%) neonates, respectively (aOR 1.40, 95% CI 0.87‐3.48). Women who were induced had a shorter postpartum admission time (2.0 vs 3.0 days ( P < 0.0001)). Conclusions: In women with a previous cesarean section and a need for delivery, induction of labor with a balloon catheter does not result in a significant increase in adverse maternal and neonatal outcomes as compared with planned cesarean section.